Efficacy and safety of probiotics combined with bismuth-containing quadruple therapy for Helicobacter pylori eradication: a systematic review and meta-analysis - Zhou, Shunhua; Yu, Yunfeng; Tian, Jiaxuan; Wang, Xiaojuan; Zeng, Meiyan; Song, Houpan (Frontiers in Microbiology, 2026)
ObjectiveHelicobacter pylori (H. pylori) infection represents a global health challenge. This study aimed to evaluate the effect of probiotic supplementation on the efficacy and safety of bismuth-containing quadruple therapy (BQT) for H. pylori eradication.MethodsRandomized controlled trials (RCTs) meeting the eligibility criteria were identified through systematic searches of five databases, including PubMed, Embase, Cochrane Library, Web of Science, and ClinicalTrials.gov. Meta-analyses were conducted using Review Manager software with a random-effects model to calculate pooled relative risks (RR) and 95% confidence intervals (CI). The potential publication bias was evaluated qualitatively, and the certainty of the evidence was subsequently assessed.ResultsIn total, 10 RCTs involving 1,630 patients were included in the analysis. The results demonstrated that, compared with the BQT group, the H. pylori eradication rate was significantly higher in the probiotics combined with the BQT group (RR 1.06, 95% CI 1.01–1.11, p = 0.009, ARR = 7.5%, NNT ≈ 13). Additionally, the combined therapy significantly reduced the adverse event rate (RR 0.58, 95% CI 0.42–0.80, p = 0.001, ARR = 11.1%, NNT ≈ 9), diarrhea (RR 0.48, 95% CI 0.32–0.73, p = 0.0007, ARR = 0.7%, NNT ≈ 142), and constipation (RR 0.53, 95% CI 0.29–0.94, p = 0.04, ARR = 2.5%, NNT ≈ 40). However, no statistically significant differences were observed for other specific adverse events, including nausea, vomiting, anorexia, heartburn, belching, taste disturbance, abdominal pain, and abdominal bloating. Sensitivity analyses confirmed the robustness of the results for the H. pylori eradication rate and adverse event rate.ConclusionCombining probiotics with BQT significantly increases the H. pylori eradication rate and reduces adverse events, particularly diarrhea and constipation. These findings support the role of probiotics as a supplementary strategy to enhance both the efficacy and safety of H. pylori eradication therapy. However, the overall certainty of the evidence is low to very low, and the optimal probiotic protocol has yet to be determined, highlighting the need for further high-quality research.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251060806, Identifier CRD420251060806.